Laser Fusion of Mouse Embryonic Cells and Intra-Embryonic Fusion of Blastomeres without Affecting the Embryo Integrity - Krivokharchenko, Alexander; Karmenyan, Artashes; Sarkisov, Oleg; Bader, Michael; Chiou, Arthur; Shakhbazyan, Avetik (PLOS ONE, 2012)
Manipulation with early mammalian embryos is the one of the most important approach to study preimplantation development. Artificial cell fusion is a research tool for various biotechnological experiments. However, the existing methods have various disadvantages, first of them impossibility to fuse selected cells within multicellular structures like mammalian preimplantation embryos. In our experiments we have successfully used high repetition rate picosecond near infrared laser beam for fusion of pairs of oocytes and oocytes with blastomeres. Fused cells looked morphologically normal and keep their ability for further divisions in vitro. We also fused two or three blastomeres inside four-cell mouse embryos. The presence of one, two or three nuclei in different blastomeres of the same early preimplantation mouse embryo was confirmed under UV-light after staining of DNA with the vital dye Hoechst-33342. The most of established embryos demonstrated high viability and developed in vitro to the blastocyst stage. We demonstrated for the first time the use of laser beam for the fusion of various embryonic cells of different size and of two or three blastomeres inside of four-cell mouse embryos without affecting the embryo’s integrity and viability. These embryos with blastomeres of various ploidy maybe unique model for numerous purposes. Thus, we propose laser optical manipulation as a new tool for investigation of fundamental mechanisms of mammalian development.